Non-neutralizing monoclonal antibody targeting VP2 EF loop of Coxsackievirus A16 can protect mice from lethal attack via Fc-dependent effector mechanism. Issue 1 (31st December 2023) - Du, Ruixiao; An, Chaoqiang; Yao, Xin; Wang, Yiping; Wang, Ge; Gao, Fan; Bian, Lianlian; Hu, Yalin; Liu, Siyuan; Zhao, Qiaohui; Mao, Qunying; Liang, Zhenglun
ABSTRACT: Coxsackievirus A16 (CA16), a main causative agent of hand, foot, and mouth disease (HFMD), has become a serious public health concern in the Asia-Pacific region. Here, we generated an anti-CA16 monoclonal antibody, DMA2017, derived from an epidemic strain CA16. Surprisingly, although DMA2017 could not neutralize the original and circulating CA16 strains in vitro, the passive transfer of DMA2017 (10 μg/g) could protect suckling mice from a lethal challenge with CA16 in vivo . Then, we confirmed the protective effect of DMA2017 relies on the Fc-dependent effector functions, such as antibody-dependent cellular cytotoxicity (ADCC). The linear epitope of DMA2017 was mapped by phage display technique to a conserved patch spanning residues 143–148 (NSHPPY) of the VP2 EF-loop of CA16. DMA2017 could inhibit the binding of the antibodies present in the sera of naturally infected children to CA16, indicating that the epitope of DMA2017 is immunodominant for CA16. Our results confirm, for the first time, that a potential preventive and therapeutic effect could be mediated by a non-neutralizing antibody elicited against CA16. These findings bring a hitherto understudied protective role of non-neutralizing antibodies during viral infections into the spotlight and provide a new perspective on the design and evaluation of CA16 vaccines.